The Louise A. Boyd expedition to East Greenland, 1933 : Photogrammetrical studies of glaciers in east Greenland / O.M. Miller, surveyor in charge - Boyd, Louise Arner, 1887-1972 (American Geographical Society of New York, 1933)
Relief shown by contours. Includes note. "Amer. Geogr. Soc. special publ. no. 18, Pl. II" -- upper right margin. Color